Pengaruh Kreativitas, Pengetahuan, dan Motivasi terhadap Inovasi Karyawan PT. Bank Pembangunan Daerah Jawa Timur Tbk Kantor Pusat Surabaya - Fira Eka Wahyuni (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The purpose of this study was to determine and analyze the impact of creativity, knowledge, and motivation on innovative employees at PT. Bank Pembangunan Daerah Jawa Timur Cantor Pusat Surabaya. This survey is a quantitative approach to 30 employees. The statistical analysis of this study is PLS (Partial Least Square) with PLS 3.0 software. The Likert Scale is used as a measurement scale. The survey results show that creativity has no significant impact on employees innovation. In addition, knowledge has not had a substantial impact on employees innovation. Motivation has a significant and positive impact on employees innovation, which causes the companies to improve their innovation through motivation continuously. Motivation has a substantial and positive effect on creativity, and knowledge has a significant and positive impact on creativity. This research is expected to have implications for improving employees' innovation by creativity, knowledge, and motivation. Companies can apply to increase employees innovation is to using extrinsic and intrinsic motivation from superiors, such as giving compensation and reward. Hence, employees feel comfortable and can generate enthusiasm in the workplace. The company should provide challenges or opportunities for employees to develop themselves either by involving them in training, workshops, or seminars to develop their creativity and knowledge or by giving them more experience and education to enhance innovation.